Targeting bile acid-activated receptors for preventing non-alcoholic fatty liver disease progression - Mohib, Mohammad Mohabbulla (2021)
Tese de mestrado, Ciências Biofarmacêuticas, Universidade de Lisboa, Faculdade de Farmácia, 2018